Review of air-based PV/T and BIPV/T systems - Performance and modelling. (January 2021) - Rounis, Efstratios Dimitrios; Athienitis, Andreas; Stathopoulos, Theodore
Abstract: This article presents a review of the monitored performance of air-based photovoltaic/thermal (PV/T) and building integrated photovoltaic/thermal (BIPV/T) systems, as well as the relevant system modelling with focus on the convective phenomena. The review showed that the majority of experimental studies involve small-scale PV/T prototypes of the stand-alone format, usually tested under conditions that are not representative of full-scale BIPV/T systems, while the cases of instrumented full-scale BIPV/T systems are very few. The varying testing conditions render a direct performance comparison of the various systems difficult, while the convective phenomena may exhibit significantly different behavior depending on the system type and size. Additionally, different expressions used to model wind-driven and channel convection may introduce significant uncertainty in the predicted performance of such systems. These inconsistencies in both the monitored and modelled performance contribute to a reduced confidence in such systems and a resulting small number of realized applications. The purpose of this review is to identify the relevant research needs pertinent to PV/T and BIPV/T testing and modelling, and in doing so provide a framework that can set the foundation for standardized testing, as well as modelling at different design stages. Highlights: BIPV/T and PV/T monitored performance. Nu expressions for channel convection from PV/T literature. Wind-driven convection for PV/T and BIPV/T. Simulated and measured results for two BIPV/T case studies. Discussion on testing and modelling of BIPV/T systems.